Non-invasive attempts to extinguish flames with the use of high-power acoustic extinguisher - Stawczyk Paweł (De Gruyter, 2021)
This paper presents an innovative method of extinguishing of flames using a high-power acoustic extinguisher. This method allows for effective and non-invasive extinguishing of the flames. Experimental results showing the effectiveness of the fire extinguisher for different distances from the flame source and different frequencies of the acoustic wave are discussed. The paper ends with the description of the advantages, disadvantages, and limitations of the proposed fire extinguishing method.